Clinical use of topical thrombin as a surgical hemostat - Wesley K Lew (Dove Medical Press, 2008)
Wesley K Lew1, Fred A Weaver21University of Southern California, Department of Surgery, Los Angeles, CA, USA; 2CardioVascular Thoracic Institute at the University of Southern California, Los Angeles, CA, USAAbstract: When surgical ligation of bleeding fails, or is not possible, surgeons rely on a number of hemostatic aids, including thrombin. This review discusses the history, pharmacology and clinical application of thrombin as a surgical hemostat. The initial thrombin was bovine in origin, but its use has been complicated by the formation of antibodies that cross react with human coagulation factors. This has been associated with life threatening bleeding and in some circumstances anaphylaxis and death. Human thrombin, isolated from pooled plasma of donors, has been developed in an effort to minimize these risks, but its downside is the potential of transmitting blood-borne pathogens and limited availability. Recently a recombinant thrombin has been developed and approved for use by the FDA. It has the advantage of being minimally antigenic and devoid of the risk if viral transmission. Thrombin is often used in conjunction with other hemostatic aids, including absorbable agents (like gelfoam, collagen, and cellulose), and with fibrinogen in fibrin glues. The last part of this review will discuss these agents in detail, and review their clinical applications.Keywords: bovine, recombinant, human, thrombin, antigenicity, antibodies